2023
DOI: 10.1371/journal.pone.0284782
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare professionals’ experiences of providing care for patients with enterocutaneous fistula in hospital and in homecare: A qualitative study

Abstract: Background Enterocutaneous fistula is a rare but complex and serious condition that is both physically and psychologically demanding for the person affected. Infection, fistula dressing problems, electrolyte and fluid imbalance and malnutrition render the individual in need of long periods of in-hospital care and homecare. This place great demands on patients, families, and healthcare professionals. More research is needed to bridge the gap between hospital and home-based healthcare services. Aim To explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The participants struggled with derangements of fluids and electrolyte balances, malnutrition, requiring increased analgesic usages, difficulty hiding feelings when changing the stoma bags, difficulty in handling sepsis, wound leakages, skin excoriations, increased fistula output, and difficulty in containing the fistula effluent. The study conducted by Härle et al 10 demonstrated similar results that the demands of ECF patients are time‐consuming and can cause physical and emotional exhaustion. The condition's complexity and complications require multidisciplinary teamwork.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The participants struggled with derangements of fluids and electrolyte balances, malnutrition, requiring increased analgesic usages, difficulty hiding feelings when changing the stoma bags, difficulty in handling sepsis, wound leakages, skin excoriations, increased fistula output, and difficulty in containing the fistula effluent. The study conducted by Härle et al 10 demonstrated similar results that the demands of ECF patients are time‐consuming and can cause physical and emotional exhaustion. The condition's complexity and complications require multidisciplinary teamwork.…”
Section: Discussionmentioning
confidence: 71%
“…The complexity of ECF complications demands a multi‐disciplinary team approach 10 . A triad of complications poses challenges for CCNs, including fluid and electrolyte abnormalities, sepsis, and malnutrition 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ECFs can occur due to various reasons, such as surgical complications, infection, perforated peptic ulcer, inflammatory bowel disease, abdominal injury, or Crohn's disease. 2,3 Approximately 60% of all ECFs tend to heal on their own within two months. However, for the remaining 40%, surgical intervention is usually required.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, for the remaining 40%, surgical intervention is usually required. 2 Despite this, the surgery is often postponed for six to 12 months after the ECF appears due to inflammation, nutritional concerns, and the need for the abdominal area to recover. This situation can be challenging for patients, their families, and medical staff.…”
Section: ■ Introductionmentioning
confidence: 99%